Volumetric analysis of hand and rotary root canal instrumentation using different obturation techniques: An in vitro spiral computed tomography study - Jatinderpal Singh; Anurag Aggarwal; Navjot Singh Mann; Ashu Jhamb (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim of this study is to volumetrically analyze the root canal volume after instrumentation with hand and rotary files and to evaluate and compare the volume percentage of root canals obturated (POV) with gutta-percha (GP), with various techniques using spiral computed tomography (SCT). Materials and Methods: Sixty sound, noncarious, single-rooted extracted human teeth were sectioned at the cementoenamel junction. The specimens were divided into five groups based on the type of canal instrumentation and obturation technique used. Specimens were prepared with Hand Files and ProTaper Next and HyFlex CM rotary Files. The volume of root canal space was measured using SCT, and root canals were obturated (cold lateral condensation, cold flowable "GuttaFlow 2," and single cone). A second SCT scan was performed to determine the POV of GP at coronal, middle, and apical third. The data were subjected to statistical analysis using one-way ANOVA and Tukey's post hoc multiple comparison tests. Results: There was a highly significant difference in percentage of obturated volume between the groups at coronal, middle, and apical third, and also, there was a highly significant difference in the total percentage of obturated volume of canal between the groups. Conclusion: No obturation technique produced void-free root canal fillings and the greatest POV was obtained with lateral condensation followed by single cone and least with cold flowable obturation technique. Lateral condensation and single-cone technique showed 100% POV in the apical third region and GuttaFlow 2 had the maximum voids.